Creating Spaces for Listening, Learning, and Sustaining the Inner Lives of Students - Gesa E. Kirsch (Journal of the Assembly for Expanded Perspectives on Learning, 2008)
This essay explores what it takes to "create a space in the classroom that allows students the freedom to nourish their inner lives," an issue raised by Mary Rose O'Reilly in Radical Presence. The author draws on work in composition studies, education, and her own teaching practices to illustrate the importance of creating such spaces.